Helicobacter pylori infection and vitamin B-12 deficiency- A cross sectional study - Ravi, K.; Joseph, Jacob; Thomas, David Mathew (Asian Journal of Medical Sciences, 2017)
Background: Vitamin B12 deficiency is a common, often overlooked medical problem in adult population. Diagnosis of vitamin B12 deficiency is incomplete without the evaluation of underlying cause. In majority of the cases Vitamin B12 deficiency is attributed to malnutrition. H. pylori infection plays an important role in the development of atrophic gastritis and related malabsorption. Hence it is suggested that there may be a relationship between h. pylori infection and vitamin B12 deficiency. Aims and Objective: To evaluate correlation of helicobacter pylori infection and blood levels of vitamin B12. Materials and Methods: A total of 120 patients with deficient serum vitamin B12 levels were evaluated. Upper GI Endoscopy was performed and gastric biopsies were obtained for Histopathological examination and histological evidence of H. pylori infection. Results: Tissue biopsy revealed chronic atrophic gastritis in 65 patients and chronic antral gastritis in 39 patients. H. pylori infection by histology was positive in 68 patients. There was significant correlation between atrophic gastritis and H. pylori as well as between H. pylori and B12 deficiency. Conclusion: H.pylori has an effect on gastric mucosa, which influences the absorption of vitamin B12. Thus individuals with B12 deficiency must be subjected for diagnostic evaluation of H.pylori infection and appropriate therapy must be initiated Asian Journal of Medical Sciences Vol.8(4) 2017 16-20